Liquid Biofuels in Latin America: Perspectives - Aponte, Gloria M. (2026)
This study analyzes the liquid biofuels market in Latin America, focusing on biodiesel and bioethanol as alternatives for decarbonizing transportation. The objective is to evaluate the regional landscape, the leading markets of Brazil and Argentina, and the state of scientific research in this area. The methodology consisted of a literature review with quantitative analysis of publications (2016-2025) and a review of data from international organizations such as the IEA and IRENA. The results highlight that Brazil leads the region, accounting for 90% of total biofuel production. A sustained regional growth of 3.7% in biofuels was identified over the last decade, driven by policies such as RenovaBio. Finally, the study concludes that the lack of stable regulatory frameworks in other countries is the main challenge to attracting private investment.